2015
DOI: 10.1002/btpr.2181
|View full text |Cite
|
Sign up to set email alerts
|

An approach for the improved immobilization of penicillin G acylase onto macroporous poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate) as a potential industrial biocatalyst

Abstract: The use of penicillin G acylase (PGA) covalently linked to insoluble carrier is expected to produce major advances in pharmaceutical processing industry and the enzyme stability enhancement is still a significant challenge. The objective of this study was to improve catalytic performance of the covalently immobilized PGA on a potential industrial carrier, macroporous poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate) [poly(GMA-co-EGDMA)], by optimizing the copolymerization process and the enzyme att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Based on the rising importance of carrier on immobilized PGA, the design and preparation of carrier have been reported extensively . According to those reports, PGA immobilization carriers can be divided into 2 broad categories, the inorganic materials and organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the rising importance of carrier on immobilized PGA, the design and preparation of carrier have been reported extensively . According to those reports, PGA immobilization carriers can be divided into 2 broad categories, the inorganic materials and organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the loading capacity ( L ), activity retention ratio ( Ar ), enzyme activity ( Ea ), response rate ( Rr ), and reusable stability ( Rs ) are main problems of immobilized PGA, because they directly affect the economic efficiency of enterprises in actual production . According to reports, the structure and composition of the carrier play an important role in above performances, so exploring and synthesizing carrier with the best suitable composition and structure have become a long‐standing goal. Although significant effort has been made on immobilized carrier for PGA, the balance among L , Ar , Rr , and Rs was still not resolved well.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peak located at 636 cm −1 is the characteristic absorption of Fe 3 O 4 , which showed the presence of Fe 3 O 4 particles in polymer microspheres. The absorption peak located at 904 cm −1 is the characteristic absorption of the epoxy groups . The results of chemical analysis indicated that PM@Fe 3 O 4 had epoxy groups of 0.11 mM/g.…”
Section: Resultsmentioning
confidence: 97%